Development and validation of a liquid chromatography–tandem mass spectrometry analytical method for the therapeutic drug monitoring of eight novel anticancer drugs. (19th December 2017) - Herbrink, M.; de Vries, N.; Rosing, H.; Huitema, A. D. R.; Nuijen, B.; Schellens, J. H. M.; Beijnen, J. H.
Abstract: To support therapeutic drug monitoring of patients with cancer, a fast and accurate method for simultaneous quantification of the registered anticancer drugs afatinib, axitinib, ceritinib, crizotinib, dabrafenib, enzalutamide, regorafenib and trametinib in human plasma using liquid chromatography tandem mass spectrometry was developed and validated. Human plasma samples were collected from treated patients and stored at −20°C. Analytes and internal standards (stable isotopically labeled analytes) were extracted with acetonitrile. An equal amount of 10 mm NH4 CO3 was added to the supernatant to yield the final extract. A 2 μL aliquot of this extract was injected onto a C18 ‐column, gradient elution was applied and triple‐quadrupole mass spectrometry in positive‐ion mode was used for detection. All results were within the acceptance criteria of the latest US Food and Drug Administration guidance and European Medicines Agency guidelines on method validation, except for the carry‐over of ceritinib and crizotinib. These were corrected for by the injection order of samples. Additional stability tests were carried out for axitinib and dabrafenib in relation to their reported photostability. In conclusion, the described method to simultaneously quantify the eight selected anticancer drugs in human plasma was successfully validated and applied for therapeutic drug monitoring in cancer patients treated with these drugs.